2019
DOI: 10.1021/acsphotonics.9b01408
|View full text |Cite
|
Sign up to set email alerts
|

Robust Vector Beam Guidance Assisted by Stress-Induced Cylindrical Anisotropy in Highly Germanium-Doped-Core Fiber

Abstract: Vector beams, structured optical beams with nonuniform polarization distributions over the cross-section, have been recently found to be more beneficial than the scalar beams to many applications ranging from super-resolution imaging and creation of strongly localized spins or magnetic resonances to multimode classical and quantum communications. The distribution of vector beams over a strand of low-cost optical fiber would alleviate the space constraint in their use and radically broaden their applications. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…61 In addition, this group has also proposed two methods to measure the mode purity of CVB 117 and VB 82 in TMFs and developed an air-core optical fiber that can support 12 distinct higher-order VBs over several kilometers. 139 Recently, Kim et al 140 also demonstrated a highly germanium-doped-core optical fiber with a step-index profile that was capable of stably guiding the RPB and APB over a wide spectral range. Due to the constraints of fiber boundary conditions, the types of singular light beams in fiber are not as abundant as that in free space, and the excitation as well as extraction of desired higher-order modes in fiber remains a long-term challenge.…”
Section: Discussionmentioning
confidence: 99%
“…61 In addition, this group has also proposed two methods to measure the mode purity of CVB 117 and VB 82 in TMFs and developed an air-core optical fiber that can support 12 distinct higher-order VBs over several kilometers. 139 Recently, Kim et al 140 also demonstrated a highly germanium-doped-core optical fiber with a step-index profile that was capable of stably guiding the RPB and APB over a wide spectral range. Due to the constraints of fiber boundary conditions, the types of singular light beams in fiber are not as abundant as that in free space, and the excitation as well as extraction of desired higher-order modes in fiber remains a long-term challenge.…”
Section: Discussionmentioning
confidence: 99%
“…106 and a large amount of literature is available on the collapse of op-tical vector fields. [107][108][109] The eigenmodes of optical fibers, including gradient-index, step-index and hollow-core photonic crystal fibers, are vector fields, 110 providing the natural choice for efficient communication links 111,112 and multiplexing. 113,114 Recent experiments have demonstrated quantum cryptography based on hybrid entanglement of polarization and orbital angular momentum in a (graded index) vortex fiber 115 and over an air-core fiber.…”
Section: Propagation In a Nonlinear Mediummentioning
confidence: 99%
“…However, the dopant concentration is often unavailable in the fiber's datasheet. One can utilize the information from multiple scientific reports [4], [5]. However, presented data are not always consistent.…”
Section: Introductionmentioning
confidence: 99%
“…However, presented data are not always consistent. For instance, references [4] and [5] specify values of GeO2 21 mol% and ~30 mol% for the same commercially available UHNA4 fiber. Therefore, to address this issue, we performed a comprehensive survey of available single-mode step-index fibers using an in-home-built characterization setup and exploiting our numerical models of the fibers.…”
Section: Introductionmentioning
confidence: 99%